2020
DOI: 10.1074/jbc.ra119.012092
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific 5-hydroxytryptophan incorporation into apolipoprotein A-I impairs cholesterol efflux activity and high-density lipoprotein biogenesis

Abstract: Apolipoprotein A-I (apoA-I) is the major protein constituent of high-density lipoprotein (HDL) and a target of myeloperoxidase-dependent oxidation in the artery wall. In atherosclerotic lesions, apoA-I exhibits marked oxidative modifications at multiple sites, including Trp72. Site-specific mutagenesis studies have suggested, but have not conclusively shown, that oxidative modification of Trp72 of apoA-I impairs many atheroprotective properties of this lipoprotein. Herein, we used genetic code expansion techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 83 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…After OSS intervention in EPCs, PSPH expression was upregulated, regulating cysteine and methionine metabolism, eventually leading to a significant decrease in Betaine. A study showed that after cells were subjected to OSS, the betaine level decreased significantly and that 5-hydroxytryptophan, a potential biomarker of DEM with reduced concentrations after experiencing OSS intervention, was incorporated into apolipoprotein A-I, impairing cholesterol efflux activity and high-density lipoprotein biogenesis ( Zamanian-Daryoush et al, 2020 ), promoting the occurrence and development of AS. β-Alanine and L-histidine are known to be involved in the synthesis of carnosine, which can delay inflammation and fight AS ( Caruso et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After OSS intervention in EPCs, PSPH expression was upregulated, regulating cysteine and methionine metabolism, eventually leading to a significant decrease in Betaine. A study showed that after cells were subjected to OSS, the betaine level decreased significantly and that 5-hydroxytryptophan, a potential biomarker of DEM with reduced concentrations after experiencing OSS intervention, was incorporated into apolipoprotein A-I, impairing cholesterol efflux activity and high-density lipoprotein biogenesis ( Zamanian-Daryoush et al, 2020 ), promoting the occurrence and development of AS. β-Alanine and L-histidine are known to be involved in the synthesis of carnosine, which can delay inflammation and fight AS ( Caruso et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, chlorination of Tyr192 has been shown to impair ABCA1-dependent RCT [56][57][58] and markedly increase atherosclerotic plaque instability [59]. ABCA1-dependent RCT was also shown to be impaired by MPO-mediated oxidation of the Trp72 residue (Trp72(O)-ApoA-I) [60], which, interestingly, accounted for 20% of the ApoA-I in atherosclerotic arteries, while the overall abundance in circulation was low [61]. Elevated Trp72(O)-ApoA-I levels demonstrated a potent pro-inflammatory activity on endothelial cells and were associated with increased CV risk [61].…”
Section: Oxidationmentioning
confidence: 99%
“…For example, differences between control subjects and patients with stable CAD or acute coronary syndrome have been established in relation to the presence of Cl-Tyr (at Tyr192) and the oxidation of Met (at Met 148) of apoA-1 [68]. The residue of Trp 72 also seems to be promising as a biomarker, since it is the subject of a multitude of studies that highlighted its importance in cholesterol efflux [44,[68][69][70][71]. It must be noted that cholesterol efflux capacity is not completely dependent on levels of functional apoA-1 [72].…”
Section: Mpo and Dysfunctional-proatherogenic Lipoproteinsmentioning
confidence: 99%
“…More recently, incorporation of site-specific oxTrp (including Trp 72) into apoA-1 has been performed [71]. By using genetic code expansion technology, noncanonical amino acid 5-hydroxytryptophan (5-OH-Trp) has been inserted at position 72 in recombinant human apoA-1.…”
Section: Modifications Of Apolipoproteinmentioning
confidence: 99%